2020
DOI: 10.1080/14397595.2020.1797283
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response among golimumab-treated Japanese patients with rheumatoid arthritis by number of previous biologic therapies: Real-world evidence from post-hoc analysis of post-marketing surveillance data

Abstract: Clinical response among golimumab-treated Japanese patients with rheumatoid arthritis by number of previous biologic therapies: Real-world evidence from post-hoc analysis of postmarketing surveillance data, Modern Rheumatology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Two cohort studies demonstrated no significant difference in persistence of GLM between biologics-naïve and biologics-experienced patients at 2 11 and 5 15 years, respectively, whereas, 3 registries from European countries have reported an increase in retention rates at 2, 17 5, 23 and 7 18 years, when GLM was used as the first-line biological therapy. Although our results are consistent with the findings of PMS 27,31 and several registries except for Japan, 17,18,23 further studies are necessary to validate these findings, particularly by including greater number of Japanese patients with longer observational periods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Two cohort studies demonstrated no significant difference in persistence of GLM between biologics-naïve and biologics-experienced patients at 2 11 and 5 15 years, respectively, whereas, 3 registries from European countries have reported an increase in retention rates at 2, 17 5, 23 and 7 18 years, when GLM was used as the first-line biological therapy. Although our results are consistent with the findings of PMS 27,31 and several registries except for Japan, 17,18,23 further studies are necessary to validate these findings, particularly by including greater number of Japanese patients with longer observational periods.…”
Section: Discussionsupporting
confidence: 89%
“…27 Additionally, further data from PMS in recent years have demonstrated that switching to GLM was effective despite the number of previously used biologics, but clinical response declined with an increasing number of prior biological therapies. 31 However, there has been limited evidence on long-term retention rates stratified by the number of prior biological therapies in routine practice. Two cohort studies demonstrated no significant difference in persistence of GLM between biologics-naïve and biologics-experienced patients at 2 11 and 5 15 years, respectively, whereas, 3 registries from European countries have reported an increase in retention rates at 2, 17 5, 23 and 7 18 years, when GLM was used as the first-line biological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The responses to medication were classified in accordance with EULAR response criteria (Supplementary data S1). A good response (GR) was defined as DAS28‐ESR ≤3.2 with a decrease of >1.2 by 6 m. A moderate response (MR) was defined as DAS28‐ESR ≤3.2 with a decrease of >0.6 and ≤1.2 by 6 m, or DAS28‐ESR ≤5.1 and >3.2 with a decrease of >0.6 by 6 m, or DAS28‐ESR >5.1 with a decrease of >1.2 by 6 m. Non‐response (NR) was defined as DAS28‐ESR >5.1 with a decrease of >0.6 and ≤1.2 by 6 m, or a decrease of ≤0.6 by 6 m [7].…”
Section: Methodsmentioning
confidence: 99%